Islamic Principles of Community Security: An Analytical Assessment of the Katsina State Community Security Watch Corps KSCSWC in Nigeria - Ammaru Ummaru (CV. FOUNDAE, 2026)
The escalation of organized banditry in northwestern Nigeria has exposed the limitations of conventional, federal-led security strategies, necessitating alternative, localized governance models. This study undertakes a critical evaluation of the operational roles of the Katsina State Community Security Watch Corps (KSCSWC) through an Islamic ethical and jurisprudential lens, addressing a significant gap in scholarly discourse by integrating faith-based principles into the analysis of grassroots security initiatives. The primary objective is to ascertain the compatibility of the Corps’ operational modalities with core Islamic tenets of public safety and communal welfare. Adopting a qualitative research methodology, the study combines analytical inquiry into classical Islamic jurisprudence with empirical fieldwork consisting of forty semi-structured interviews and direct observation in Katsina State. The data collected was subjected to thematic analysis. The findings reveal that the KSCSWC’s operational successes in intelligence gathering, neutralizing criminal elements, and deterring crime are deeply aligned with Islamic principles of communal security (ḥirāsah and ribāṭ). These interventions have led to tangible improvements in public safety, facilitating a revitalization of local economies, agriculture, and education. The paper concludes that anchoring local security frameworks within regional religious ethics substantially augments community cooperation and operational legitimacy. It recommends expanding the Corps' mandate to include offensive operations, optimizing rural deployment, and institutionalizing ethical training.